The Effect of Penguin Exercise on the Anxiety Levels of Female Students Who Experience Premenstrual Syndrome - Handoyo, Handoyo; Hartati, Hartati; Widayanti, Esti Dwi (Jurnal Keperawatan Soedirman, 2020)
Premenstrual syndrome includes a variety of abnormal physical, psychological, and emotional symptoms associated with a woman's menstrual cycle. The syndrome can interfere with several aspects of womenâ€™s lives and lead to a decrease in work productivity and concentration in school, as well as anxiety and depression.The aim of this study was to determine the effect of Penguin exercise on the anxiety levels of young women who experience premenstrual syndrome. This type of research was Quasi Experimental using pre and post test design with a control group. The population of this study were all 8th grade students at SMP N 9 Purwokerto. The sampling technique was simple random sampling. The instrument used to assess anxiety levels was the Taylor Manifest Anxiety Scale (TMAS) questionnaire. Analysis of the data was performed using Wilcoxon's rank sum test.Â The results showed that Penguin exercise had a significant effect on the level of anxiety in the treatment group (value p = 0,000) and there was no significant effect on the control group (p value = 0.233). The conclusion of this study is that Penguin exercise can affect the anxiety levels of 8th grade female students at SMP N 9 Purwokerto who experience premenstrual syndrome.Â